2008
DOI: 10.2460/javma.232.8.1206
|View full text |Cite
|
Sign up to set email alerts
|

Hematuria and transitional cell papilloma of the renal pelvis treated via unilateral nephrectomy in an alpaca

Abstract: Although anemia is common in South American camelids, hematuria is an uncommon sign of this condition. Chronic urinary tract infection, toxin ingestion, and neoplasia causing hematuria or hemoglobinuria should be considered in South American camelids with pigmenturia. Thorough and systematic evaluation of the urinary tract should be performed to locate the site of hemorrhage to treat hematuria appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A case report in cattle showed that unilateral nephrolithiasis might not be associated with azotemia ( 23 ), which might be possible as long as there is no obstruction of the distal urinary passages. There is evidence showing that alpacas can live without restrictions after unilateral nephrectomy ( 24 ) as other ruminants do ( 25 ). In these two previously mentioned case reports, unilateral nephrectomy was not associated with azotemia.…”
Section: Discussionmentioning
confidence: 99%
“…A case report in cattle showed that unilateral nephrolithiasis might not be associated with azotemia ( 23 ), which might be possible as long as there is no obstruction of the distal urinary passages. There is evidence showing that alpacas can live without restrictions after unilateral nephrectomy ( 24 ) as other ruminants do ( 25 ). In these two previously mentioned case reports, unilateral nephrectomy was not associated with azotemia.…”
Section: Discussionmentioning
confidence: 99%
“…Urinalysis did reveal struvite crystals and urine culture yielded light growth of Enteroccoccus sp. Other considerations for bladder masses in ruminants include exposure to environmental toxins, viral associated papilloma, and neoplasia 18–22 . Bovine papilloma virus Type 2 has been associated with development of bladder neoplasia in cattle especially when grazing bracken fern plants 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Hematuria was the presenting complaint in an 11-year-old alpaca having transitional cell papilloma of the renal pelvis. 45 Nephrectomy was successful to resolve clinical signs. Also, unilateral nephrectomy was successful for treatment for ectopic ureter in a juvenile llama.…”
Section: Simple Herniasmentioning
confidence: 96%